Significance of rubella virus infection in juvenile chronic polyarthritis. - Schnitzer, T J (1977)
Fifty-three patients under the age of 5 years with definite juvenile chronic polyarthritis (JCP) were examined for serological evidence of rubella infection. The prevalence of rubella antibody was found to be low and did not differ significantly from that found in normal children of similar age. Patients with JCP and antibody to rubella virus had a clinical course indistinguishable from those with no detectable rubella antibody.